An unexpected complication of hypoglossal schwannoma surgery: Cerebrospinal fluid leakage—A case report and literature review - ASYA, ORHAN; KUYUMCU, ÖMER FARUK; GÜNDOĞDU, YAVUZ (My University, 2023)
Background: Extracranial hypoglossal schwannoma is a rare tumor primarily treated with surgical excision. This article aims to highlight the potential for unexpected complications intraoperatively, such as cerebrospinal fluid leakage from skullbase to neck. Methods: A previously healthy 23-year-old male presented with tongue numbness. Magnetic resonance imaging revealed a 17 × 20 mm nodular lesion adjacent to the cervical segment of the internal carotid artery. Surgical excision was scheduled due to suspicion of a neurogenic tumor. Results: Intraoperatively, despite careful handling, cerebrospinal fluid leakage was observed. Manipulation of the mass caused detachment of proximal nerve fibers, potentially indicating avulsion of the hypoglossal nerve from the brainstem or nearby. Clear fluid leakage from the skull base was also noted. Conclusion: Thorough preoperative evaluation and patient education regarding potential complications are crucial. This article presents an unexpected complication encountered during surgical excision of extracranial hypoglossal schwannoma, emphasizing the need for awareness and preparedness in such cases.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; Otorhinolaryngology; avulsion; cerebrospinal fluid leakage; hypoglossal schwannoma; neck tumor; surgery